2000
DOI: 10.1046/j.1469-7580.2000.19620285.x
|View full text |Cite
|
Sign up to set email alerts
|

Galanin‐like immunoreactive endocrine cells in bovine pancreas

Abstract: Pancreata of fetal, neonatal and adult cattle were studied immunohistochemically for galanin. The results revealed galanin-like immunoreactivity both in the endocrine cells and in the neural elements. The galaninlike immunoreactive endocrine cells (Gal-LIEC) were confined to the large islets, and were not observed in the islets of Langerhans and exocrine pancreas. They were first detected at the third prenatal month. Their developmental profile showed an increase from fetal to early neonatal stage with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…It also confirmed previous findings on its presence not only in the neural elements but also in the large islet endocrine cells of cattle [2,17]. The Gal-IR endocrine cells in the large islets may be a peculiar morphological feature of the large but not the small ruminant species.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…It also confirmed previous findings on its presence not only in the neural elements but also in the large islet endocrine cells of cattle [2,17]. The Gal-IR endocrine cells in the large islets may be a peculiar morphological feature of the large but not the small ruminant species.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, a sharp increment to maximum in the volume density of Gal-IR endocrine cells in the large islets of cattle was also observed precisely at this period [2]. It may be suggested that galanin, either as a neural element or endocrine cell constituent, exerts its most influential role during the perinatal development of cattle wherein substantial metabolic alteration occurs as the animal system adapts from intra-to extra-uterine life.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations